Case Report: Challenges in immunotherapy for the elderly: a case of refractory ICI-induced AIHA and thrombocytopenia in advanced gastric cancer - Yu, Mingxin; Ding, Yanhong; Ji, Linlin; Zhang, Yi; Wu, Kun; Zhang, Junying; Cao, Rongxuan; Liu, Yang; Bian, Yandong; Shen, Xin; Nie, Yuhui; Gao, Yanfang; et al. (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer immunotherapy. However, immune-related adverse events (irAEs), particularly hematologic toxicities, remain rare but potentially life-threatening complications. Among these, autoimmune hemolytic anemia (AIHA) induced by ICIs is a clinically significant yet underrecognized condition. We report a rare case of ICI-induced AIHA concomitant with thrombocytopenia in an elderly female patient with advanced gastric cancer who had undergone immune monotherapy.Case descriptionAn 84-year-old female with unresectable, PD-L1–high (combined positive score [CPS] = 55) advanced gastric adenocarcinoma developed a rare case of recurrent immune checkpoint inhibitor associated autoimmune hemolytic anemia and thrombocytopenia after sequential treatment with three ICIs: sintilimab (anti–PD-1), cadonilimab (a bispecific PD-1/CTLA-4 antibody), and ivonescimab (a bispecific PD-1/VEGF antibody). Initially, sintilimab monotherapy induced partial tumor regression; however, the patient later developed transfusion-dependent anemia and severe thrombocytopenia. Bone marrow aspiration revealed erythroid aplasia and characteristic teardrop poikilocytes, suggesting marrow stress or fibrosis. Reintroduction of ICIs triggered recurrent hematologic toxicity, pointing to a class-wide immune-mediated mechanism. Despite aggressive treatment with glucocorticoids, red blood cell and platelet transfusions, and comprehensive supportive care, the cytopenias persisted, and imaging confirmed disease progression. Ultimately, immune-related hematologic toxicity led to multiorgan failure and the patient’s death.ConclusionThis case underscores the diagnostic complexity and therapeutic challenges associated with immune checkpoint inhibitor induced autoimmune hemolytic anemia in elderly patients, particularly those experiencing immunosenescence and possessing limited hematopoietic reserve. The mechanisms underlying this phenomenon remain poorly understood, highlighting the urgent need for mechanistic investigations, individualized immunotherapeutic strategies, and vigilant hematologic monitoring in vulnerable populations.